2007
DOI: 10.1614/wt-07-016.1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nimblewill (Muhlenbergia schreberi) Control in Cool-Season Turfgrass

Abstract: Isoxaflutole and mesotrione have been used to control creeping bentgrass in cool season turf, these experiments evaluate these two products for selective nimblewill control. Three experiments were conducted in Virginia and Tennessee to evaluate selective control options for nimblewill in cool-season turfgrass. Single applications of isoxaflutole control nimblewill more effectively than single applications of mesotrione. Nimblewill control 8 wk after initial treatment (WAIT) increased as mesotrione rates increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Likewise, McElroy and Breeden (2005) reported that tall fescue injury from mesotrione applications peaked 1 wk after treatment and had dissipated by 2 wk after initial treatment (WAIT). Askew et al (2004) and Willis et al (2005) Control was visually estimated as a percentage reduction of green tissue compared to nontreated plots due to the combined effects of discoloration, necrosis, and stand reduction at 22, 9, and 8 weeks after initial treatment for broadleaf plantain, henbit, and yellow woodsorrel, respectively. b Each mean represents the average of four different treatment combinations including full rate preemergence, half rate preemergence, half rate preemergence followed by quarter rate early postemergence, and quarter rate preemergence, early postemergence, and late postemergence.…”
Section: Effects Of Treatment Combinations On Herbicidementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, McElroy and Breeden (2005) reported that tall fescue injury from mesotrione applications peaked 1 wk after treatment and had dissipated by 2 wk after initial treatment (WAIT). Askew et al (2004) and Willis et al (2005) Control was visually estimated as a percentage reduction of green tissue compared to nontreated plots due to the combined effects of discoloration, necrosis, and stand reduction at 22, 9, and 8 weeks after initial treatment for broadleaf plantain, henbit, and yellow woodsorrel, respectively. b Each mean represents the average of four different treatment combinations including full rate preemergence, half rate preemergence, half rate preemergence followed by quarter rate early postemergence, and quarter rate preemergence, early postemergence, and late postemergence.…”
Section: Effects Of Treatment Combinations On Herbicidementioning
confidence: 99%
“…Gmel.) (Willis et al 2005) without significantly injuring cool-season turfgrasses. Owing to the need to fill voids in the turfgrass canopy after weedy grasses are controlled, preliminary greenhouse and field trials were conducted in Virginia to test isoxaflutole and mesotrione for safety at seeding of tall fescue (Askew and Beam 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is a native warm-season (C 4 ) perennial grass that thrives in lightly shaded areas and easily invades lawns, waste areas, and other disturbed sites [3]. Controlling nimblewill with herbicides is difficult and the weed presents a serious problem in horse pastures.…”
Section: Introductionmentioning
confidence: 99%
“…It is a native warmseason or C 4 perennial grass that thrives in lightly shaded areas and easily invades lawns, waste areas, and other disturbed sites [3]. In unmowed areas, nimblewill can grow to 20 -60 cm in height; however, it is more aggressive in shaded areas with a moist, rich soil.…”
Section: Introductionmentioning
confidence: 99%
“…In unmowed areas, nimblewill can grow to 20 -60 cm in height; however, it is more aggressive in shaded areas with a moist, rich soil. Nimblewill spreads by seeds and has slender culms that fall to the ground and root at nodes; however, the plants do not have true rhizomes or stolons [3]. Nimblewill is difficult to control with herbicides and poses a serious problem in pastures.…”
Section: Introductionmentioning
confidence: 99%